Analisis Kesalahan Berbahasa dalam Tataran Fonologi pada Video Youtube Bule Barbie “Ngomong Bahasa Indonesia 24 Jam? Bule Barbie Jadi Bingung” - Diliana, Ekfindar; Mangunsong, Tio Artha Mega (TSAQOFAH, 2023)
Social media platforms like YouTube have gained popularity as a means of disseminating linguistic content. When foreigners, like "Bule Barbie," attempt to speak Indonesian, some missed-pronounce often occurs. the objectives of this study are to: (1) characterize the mispronounced language sounds in the Bule Barbie YouTube video; and (2) pinpoint the contributing elements to these mispronounced language sounds. Speech with linguistic mistakes made up the research's data. The primary data for this study were from the speech in Bule Barbie YouTube channel on August 14, 2023, entitled "Speaking Indonesian 24 Hours? "Bule Barbie So Confused," while the secondary data were from a variety of sources, including books, journals and other sources that offer data pertinent to the ongoing investigation. There are several kinds of linguistic mistakes, including additions, deletions, and alterations. Various variables, including the effect of one's native language, lack of Bahasa Indonesia mastery, and a lack of formal education, contribute to these inaccuracies. Reducing language errors can be achieved by understanding the sentence structure of Bahasa Indonesia, expanding vocabulary, communicating with native speakers, using learning resources, getting feedback, enrolling in a language class, and practicing regularly.